Challenge, threat, coping potential: How primary and secondary appraisals of job demands predict nurses' affective states during the COVID‐19 pandemic - Martha Fernandez De Henestrosa; Philipp E. Sischka; Georges Steffgen (Wiley, 2023)
Abstract Aim The COVID‐19 pandemic has led to a rapid raise of work‐related stress among nurses, affecting their emotional well‐being. This study examined how nurses appraise job demands (i.e. time pressure, emotional demands and physical demands) during the pandemic, and how primary (i.e. challenge and threat) and secondary appraisals (i.e. coping potential) of job demands predict nurses' affective states (i.e. positive affect, anger and anxiety). Design A cross‐sectional online survey. Methods 419 nurses completed self‐report measures of job demands and related appraisals. Data analyses comprised correlation analysis, factor analysis, hierarchical linear regression analysis and dominance analysis. Results Emotional and physical demands correlated exclusively with threat appraisal, while time pressure correlated with challenge and threat appraisal. Time pressure, emotional demands and threat appraisals of job demands predicted negative affective states, while challenge appraisals of emotional and physical demands predicted positive affect. Coping potential was identified as the most important predictor variable of nurses' affective states. Public Contribution The current study identified statistically significant risk and protective factors in view of nurses' affective states experienced during the COVID‐19 pandemic.